Altered expression of circadian clock genes during peripheral blood stem cell mobilization induced by granulocyte colony-stimulating factor. (August 2015) - Sugiyama, Akiko; Yujiri, Toshiaki; Tanaka, Mayumi; Tanaka, Yoshinori; Nakamura, Yukinori; Tanizawa, Yukio
<x xml:space="preserve">Abstract</x> Circulating hematopoietic stem cells exhibit robust circadian fluctuations, which influence the mobilized cell yield, even during enforced stem cell mobilization. However, alterations in the expression of circadian clock genes during granulocyte colony-stimulating factor (G-CSF)-induced peripheral blood stem cell (PBSC) mobilization are not fully elucidated. Therefore, we measured the expression of these genes in human peripheral blood leukocytes from 21 healthy donors. While CRY1 mRNA expression significantly increased by 3.9-fold (p < 0.01), the expression of PER3, CRY2 and BMAL1 mRNAs significantly decreased (by 0.2-fold, 0.2-fold, and 0.6-fold, respectively; p < 0.001) after G-CSF administration. Moreover, CRY1 mRNA expression was inversely correlated with the plasma level of noradrenaline (r = −0.36, p < 0.05), while PER3, CRY2, and BMAL1 mRNA expression directly correlated with the plasma level of noradrenaline (r = 0.55, r = 0.66, and r = 0.57, respectively; p < 0.001). Thus, significant correlations between the levels of circadian clock gene mRNAs and the plasma level of noradrenaline, a sympathetic nervous system neurotransmitter, were established. The modulation of sympathetic activation and of the circadian clock may be novel therapeutic targets for increasing stem cell yields in PBSC donors.